2012
DOI: 10.1093/ntr/ntr252
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Probability Discounting by Cigarette Smokers Following Acute Smoking Abstinence

Abstract: Introduction: Given the lack of consensus regarding changes in temporal and probability discounting as a function of smoking abstinence in cigarette smokers, the present study comprehensively examined possible changes in these processes following a period of acute smoking abstinence consistent with elevated withdrawal symptoms and craving. Methods:Computerized temporal and probability discounting assessments were collected from cigarette smokers following normal smoking and 24-hr smoking abstinence, with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 69 publications
3
64
2
Order By: Relevance
“…For example, environmental drug cues significantly increased demand for alcohol and tobacco (Acker & Mackillop 2013; MacKillop et al 2010b, 2012b), suggesting that drug-related associative conditioning leads to dynamic increases in demand. Similarly, acute withdrawal from nicotine significantly increased tobacco demand (MacKillop et al 2012b) and also made increased discounting even more precipitous among smokers and opiate-dependent individuals (Field et al 2006, Giordano et al 2002, Mitchell 2004, Yi & Landes 2012). In a preclinical study, a parallel relationship was reported in which morphine withdrawal increased demand for a substitute opiate (Wade-Galuska et al 2011).…”
Section: Processes Engendering Reinforcer Pathologymentioning
confidence: 99%
“…For example, environmental drug cues significantly increased demand for alcohol and tobacco (Acker & Mackillop 2013; MacKillop et al 2010b, 2012b), suggesting that drug-related associative conditioning leads to dynamic increases in demand. Similarly, acute withdrawal from nicotine significantly increased tobacco demand (MacKillop et al 2012b) and also made increased discounting even more precipitous among smokers and opiate-dependent individuals (Field et al 2006, Giordano et al 2002, Mitchell 2004, Yi & Landes 2012). In a preclinical study, a parallel relationship was reported in which morphine withdrawal increased demand for a substitute opiate (Wade-Galuska et al 2011).…”
Section: Processes Engendering Reinforcer Pathologymentioning
confidence: 99%
“…In general, performance in delay and/or probability discounting tasks is associated with several maladaptive behaviors, including drug use and pathological gambling. For example, drug abusers show greater discounting of delayed monetary rewards relative to non-abusers (Bickel et al 1999; Coffey et al 2003; Madden et al 1997; Mitchell 1999; Vuchinich and Simpson 1998), although other studies show that drug users and non-users do not differ in probability discounting (Andrade and Petry 2002; Mitchell 1999; Ohmura et al 2005; Reynolds et al 2007; Yi and Landes 2012). Pathological gamblers show steeper discounting of delayed reinforcement and respond more for large, uncertain reinforcers relative to small, certain reinforcers (Madden et al 2009; Petry 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Abstinence increases delay discounting 31,32 and causes smokers to overestimate time. 33,34 Although sex may be an important factor in impulsive decisionmaking and time perception, no study has investigated whether sex moderates abstinence effects on impulsive decision-making and time perception.…”
Section: Introductionmentioning
confidence: 99%